Exosomes from hypoxia-treated human adipose-derived mesenchymal stem cells enhance angiogenesis through VEGF/VEGF-R. (April 2019) - Han, Yudi; Ren, Jing; Bai, Yun; Pei, Xuetao; Han, Yan
Highlights: We study protective effect of hypoxia-ADSC-derived exosome on fat graft. HypADSC-Exo had higher levels of growth factors than normoxia-ADSC exosome. HypADSC-Exo dramatically improved neovascularization around the graft tissue. HypADSC-Exo increased the protein expressions of VEGF/VEGF-R in the grafted tissue. Abstract: Background: We previously reported that co-transplantation of exosomes from hypoxia-preconditioned adipose mesenchymal stem cells (ADSCs) improves the neoangiogenesis and survival of the grafted tissue. This study aimed to investigate the molecular mechanism of this protective effect. Methods: Exosomes were collected from normoxia-treated (nADSC-Exo) or hypoxia–treated (hypADSC-Exo) human ADSCs, and their pro-angiogenic capacity was evaluated in human umbilical vein endothelial cells (HUVECs) and a nude mouse model of subcutaneous fat grafting. Protein array was used to compare the exosome-derived proteins between nADSC-Exo and hypADSC-Exo. Results: Compared with the nADSC-Exo group and untreated control, hypADSC-Exo treatment significantly promoted proliferation, migration and tube-formation capability of HUVECs. Protein array revealed that the levels of vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), fibroblast growth factor (FGF) and their receptors (VEGF-R2, VEGF-R3), and monocyte chemoattractant protein 2 (MCP-2), monocyte chemoattractant protein 4 (MCP-4) were significantly higher in the hypADSC-Exo than in the nADSC-Exo. In the nude mice model of fat grafting, immunofluorescence of CD31 showed that hypADSC-Exo dramatically improved neovascularization around the graft. Furthermore, compared with nADSC-Exo and control groups, cotransplantation of hypADSC-Exo significantly increased the protein expression of EGF, FGF, VEGF/VEGF-R, angiopoietin-1(Ang-1) and tyrosine kinase with immunoglobulin-like and EGF-like domains 1(Tie-1, an angiopoietin receptor) in the grafted tissue at 30 days after transplantation. Immunohistochemical analysis demonstrated that hypADSC-Exo treatment significantly increased VEGF-R expression in the grafted tissue. Conclusions: Exosomes from hypoxia-treated human ADSCs possess a higher capacity to enhance angiogenesis in fat grafting, at least partially, via regulating VEGF/VEGF-R signaling.